Pembelajaran Matematika Berbasis Multimedia dan Interaktif - Setiawi, Agustina Purnami; Edwin, Edwin; Mau, Stefanus Dwi Istiavan; Sabawaly, Diana Reby (Varied Knowledge Journal, 2024)
This study aims to evaluate the effectiveness of multimedia and interactive-based mathematics learning at SMKS Pancasila Tambolaka, specifically for students in the Tourism Service Management program in Sumba Barat Daya. By combining quantitative and qualitative approaches (mixed methods), this research measures the improvement in students' understanding of mathematical concepts as well as their perceptions of this teaching method. Quantitative data was collected through pre-tests and post-tests to compare students' understanding before and after the multimedia-based learning, while a Likert scale questionnaire was used to assess students' motivation and satisfaction. Qualitative data was gathered through in-depth interviews with teachers and focus group discussions with students to capture their experiences. The results indicate that multimedia and interactive learning methods significantly enhance students' understanding of mathematical concepts, as well as strengthen their motivation and participation in class. Teachers also reported benefits from using this technology, which helps to simplify abstract concepts. Recommendations from this study include improving technology infrastructure and providing ongoing teacher training to ensure optimal implementation. These findings support previous research, which suggests that multimedia is effective in enhancing the quality of learning and increasing student engagement.